Pengolahan Limbah Jasa Pencucian Kendaraan dengan Metode Koagulasi-Flokulasi - Rusdi Rusdi; Wardalia Wardalia (Seminar Nasional Teknik Kimia Kejuangan, 2016)
The treatment of wastewater generated from washing service businees of motor vehicles (WSBMV) by using coagulation and flocculation method was presented in this paper. The purposes of this research were to obtain fresh water (recycle)through treating of wastewater from WSBMV and determine the best dose of each parameter.The wastewater used in this research was obtained from washing service businees “Shop & Drive, NMA Motor” located in Cilegon city.This research was conducted using Jar Test in Laboratory PT. Krakatau Tirta Industri, parameters measured were TSS and surfactants water. Coagulants used were Alum (Al2SO4) 1% and PAC (Poly Alumunium Chlorida) 1%. The dose of coagulantswas varied in ranging of 10 mg/l, 20 mg/l, and 30 mg/l with the conditions of waste without sedimentation and sedimentation for 30 minutes.The results showed thatThe biggest TSS (Total Suspended Solid) removal (99.408%) was obtained at PAC 30 mg/L and sedimentation 30 minutes. Whereas, the biggest surfactant removal (99.976%) was obtained at PAC 10 mg/L and without sedimentation.